Pengujian Tingkat Kepatuhan Pembayaran Pajak Penghasilan Wajib Pajak Orang Pribadi Non Karyawan - Kristian Agung Prasetyo (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2011)
In a tax sytem where taxpayers activerly report, calculate, and ultimately pay their own taxes, it is clear that tax cheating is always a problem. As a result, extensive works on this topic have been made. We can see for instance the standard ecenometrical model developed by Allingham and Sadmo. These writers, ion aessence, argue that a taxpayer faces as dilemma whether he will report all or part of this icome at the time af tax return lodgment. The decision would depend on several factors but mainly they are the probability pf detection and the amount of penalty rate. a decision to cheat would be taken if its possible risks are lower than the benefits. This research looksat the same tofic for individual no-employee taxpayers in Tangerang. The results generally show that these taxpayers tend to pay tax lower in its proportion of their gross income. The analysis also reveals that midldle income taxpayers are more likely to engange in tax-cheating game while taxpayers that belong to the lower and higher the income, the lower groups are less likely to do so in general, howewer, the higher the income, the lower the amount of taxes that they pay relative to their gross income . This is consistent with the theory predicition as long as the relative risk aversion decreases with income.